Comparison of outcome in lumbar spine instability treated surgically with pedicle screw fixation with or without interbody fusion device (cage) - Kumar Mishra, Sandeep; Haresh Gori, Kushal; C. E., Deepak (International Journal of Research in Medical Sciences, 2018)
Background: Lumbar spinal fusion was introduced approximately 70 years ago and has evolved as a treatment option for symptomatic spinal instability, spinal stenosis, spondylolisthesis, and degenerative scoliosis. Broader applications including use as a treatment of chronic low back pain and recurrent radiculopathy have resulted in a dramatic increase in the rates of lumbar fusion procedures within the last decade. Methods: A retrospective and prospective study to be carried out for 40 patients who were assigned in the following groups: Group 1 (n=20) consisted of patients who underwent lumbar interbody fusion with pedicle screw and bone graft, and Group 2 (n=20) consisted of patients treated by lumbar interbody fusion with pedicle screw and interbody cage. Results: Most of patients with lumbar spine instability were in 4th and 5th decade of life with average age of 46.75 yrs and female predominance with 26 (65%) cases.65% of Instability was found due to Spondylolisthesis. PLIF with Cage showed better scores than BG in terms of ODI, VAS, SF-36, Benzel’s modified Japanese scores at end of 1 year, which is statistically not significant. Conclusions: Lumbar spine instability is more common in 4th and 5th decade of life with female predominance, commonest level of instability being L4-L5 and commonest mode was Spondylolisthesis. PLIF with Cage is associated with greater operative time and lesser blood loss. Patients with PLIF + Cage had better neurological improvement, pain reduction, reduced disability, generalised well-being and satisfaction as evident by Modified Benzel’s Japanese scales, VAS, ODI, and SF-36 scores respectively, which is statistically not significant. Addition of an interbody fusion device (Cage) helps in greater stability, lower implant failure, higher fusion rate and better functional outcome in patient treated with PLIF for lumbar spine instability.